Knock-down of synapsin alters cell excitability and action potential waveform by potentiating BK and voltage-gated Ca2+ currents in Helix serotonergic neurons. (17th December 2015) - Brenes, O.; Vandael, D.H.F.; Carbone, E.; Montarolo, P.G.; Ghirardi, M.
Highlights: Cell excitability of single synapsin-silenced neurons was analyzed in vitro . Synapsin-silenced single neurons showed an increased intrinsic excitability. Increased Ca 2+ currents are related with faster firing in synapsin-silenced cells. Increased BK currents are associated with faster firing in synapsin-silenced cells. Abstract: Synapsins (Syns) are an evolutionarily conserved family of presynaptic proteins crucial for the fine-tuning of synaptic function. A large amount of experimental evidences has shown that Syns are involved in the development of epileptic phenotypes and several mutations in Syn genes have been associated with epilepsy in humans and animal models. Syn mutations induce alterations in circuitry and neurotransmitter release, differentially affecting excitatory and inhibitory synapses, thus causing an excitation/inhibition imbalance in network excitability toward hyperexcitability that may be a determinant with regard to the development of epilepsy. Another approach to investigate epileptogenic mechanisms is to understand how silencing Syn affects the cellular behavior of single neurons and is associated with the hyperexcitable phenotypes observed in epilepsy. Here, we examined the functional effects of antisense-RNA inhibition of Syn expression on individually identified and isolated serotonergic cells of the Helix land snail. We found that Helix synapsin silencing increases cell excitability characterized by a slightly depolarized resting membrane potential, decreases the rheobase, reduces the threshold for action potential (AP) firing and increases the mean and instantaneous firing rates, with respect to control cells. The observed increase of Ca 2+ and BK currents in Syn-silenced cells seems to be related to changes in the shape of the AP waveform. These currents sustain the faster spiking in Syn-deficient cells by increasing the after hyperpolarization and limiting the Na + and Ca 2+ channel inactivation during repetitive firing. This in turn speeds up the depolarization phase by reaching the AP threshold faster. Our results provide evidence that Syn silencing increases intrinsic cell excitability associated with increased Ca 2+ and Ca 2+ -dependent BK currents in the absence of excitatory or inhibitory inputs.